Dean vortex ultraviolet light pasteurization of pummelo (Citrus Grandis L. Osbeck) fruit juice - Abdul Karim Shah, Nor Nadiah (2015)
Pummelo juice has long been believed to have a connection with good health, due to their antioxidant potency and plasma lipid metabolism. Therefore, giving Malaysia an attractive opportunity to expand its influence and marketability in the international market of juices. However, conventional thermal pasteurization has been known to induce unfavorable changes to fruit juice. Thus, ultraviolet (UVC) light system is introduced as an alternative non-thermal pasteurization method to pummelo fruit juice as it is deemed suitable due to its small carbon footprints with other contributing factors such as cost saving, environmental friendly and non-toxic. The overall aims of this research was to pasteurize pummelo fruit juice using a dean vortex UVC system to produce a healthy and safe juice with its original nutritional content intact. Therefore, the research was done in stages; where the first stage was to choose an optimum pummelo variety suitable for juice production. In the second stage,clarification treatment was done on the chosen variety to increase the clarity and subsequently, lowering the absorption coefficient of pummelo fruit juice with minimal pectin methylesterase activity. Hence forth, performance of dean vortex UVC reactor was experimentally validated with the results of Computational Fluid Dynamics (CFD) to evaluate the reactor’s pasteurization efficiency. In the forth stage, the ability of this technology was evaluated to inactivate Salmonella typhimurium to a minimum of 5log10 reduction. The technology was further exploited in the fifth stage, with investigation of post-UVC treatment effect on physicochemical characteristics,antioxidant capacity and most importantly, furan development of clarified pummelo fruit juice. These areas have not been explicitly explored in specifics to pummelo fruit juice in previous literatures. From the study, UVC fluence was observed to be absorption-coefficient-dependent where, it varies according to liquid samples. UVC fluence was found to be highly correlated (R2 = 91%, p <0.05) towards retention time distribution (RTD), following Lambert-Beer’s equation, which implies the UVC transmission throughout the clarified juice is ideal. The results from computational fluid design has validated the previous result that clarified juice with low absorption coefficient emulated an ideal liquid where the centrifugal forces that act on the juice is higher, thus creating an ideal mixing condition within the convoluted tube. Low velocity demonstrated by fresh juice sample, had increased the total heat transfer rate which in turn increased the processing cost and elevating temperature which could render UVC pasteurization futile. UVC fluence was observed to be inversely proportional to velocity, temperature and liquid flow rate. Therefore, in order to produce an effective UVC pasteurization, combination of high flow rate with adequate RTD is imperative to stabilize the temperature of UVCtreated sample. UVC fluence of 28.15, 27.63 and 133 mJ/cm2 respectively for fresh, clarified juice and distilled water was observed to be adequate to inactivate with more than 5log10 inactivation after one-pass of UVC treatment. Salmonella typhimurium reduction was also observed to be inversely proportional to liquid’s flow rate with coefficient of determination, R2 ranged from 83 to 99%. Moreover, coefficient of determination, R2 of processing energy to inactivate Salmonella typhimurium in clarified juice was found to be higher (99%) and significant (p <0.05) in comparison to fresh juice (93%). Post- UVC treatment, color L* was seen to increase as pectin methylesterase activity in the UVC-treated juice had decreased (p <0.05). In addition to that, ascorbic acid content was observed to decrease together with total phenolic contents and total soluble solids. UVC treatment also had a significant (p <0.05) effect on the amount of antioxidant capacity of UVC-treated pummelo juice (DPPH, FRAP and ABTS) and its decrement is highly correlated to UVC-treatment and storage life. Furan development within the juice post-UVC treatment (between 0.66 to 2.4 ppb/ml) was seen to be dose and temperature-dependent (p <0.05). However, the amount of furan found in the UVCtreated juice was deemed minimal in comparison to data published on thermally-treated fruit juice. Thus, clarified pummelo juice with absorption coefficient, α of 17 cm-1 can be safely treated with a maximum of 30 mJ/cm2 UVC fluence using dean vortex UVC system and its storage life was prolonged to 6 weeks in comparison to less than a week for freshly-squeezed non-pasteurized pummelo fruit juice.